Characteristics, management, and outcomes of patients with lung cancer admitted to a tertiary care intensive care unit over more than 20 years - Al-Dorzi, Hasan M.; Atham, Sadeem; Khayat, Faten; Alkhunein, Jullanar; Alharbi, Bushra T.; Alageel, Norah; Tlayjeh, Mohamed; Tlayjeh, Haytham; Arabi, Yaseen M. (Annals of thoracic medicine, 2024)
Abstract RATIONALE: The prognosis of patients with lung cancer admitted to the intensive care unit (ICU) is often perceived as poor. We described the characteristics, management, and outcomes of critically ill patients with lung cancer and determined the predictors of mortality. METHODS: We retrospectively studied patients with lung cancer who were admitted to the ICU of a tertiary care hospital between 1999 and 2021 for the reasons other than routine postoperative care. We noted their characteristics, ICU management, and outcomes. We performed the multivariable logistic regression analysis to determine the predictors of hospital mortality. RESULTS: In the 23-year period, 306 patients with lung cancer were admitted to the ICU (median age = 63.0 years, 68.3% males, 45.6% with moderate/severe functional disability, most had advanced lung cancer, and median Acute Physiology and Chronic Health Evaluation II score = 24.0). Life support measures included invasive mechanical ventilation (47.1%), vasopressors (34.0%), and new renal replacement therapy (8.8%). Do-Not-Resuscitate orders were implemented during ICU stay in 30.1%. The hospital mortality was 43.8% with a significantly lower rate in patients admitted after 2015 (28.0%). The predictors of mortality were moderate/severe baseline disability (odds ratio [OR] 2.65, 95% confidence interval [CI] 1.22, 5.78), advanced lung cancer (OR 8.36, 95% CI 1.81, 38.58), lactate level (OR 1.45, 95% CI 1.12, 1.88, invasive mechanical ventilation (OR 10.92, 95% CI 4.98, 23.95), and admission period after 2015 (OR 0.37, 95% CI 0.16, 0.85). CONCLUSIONS: The mortality rates in patients with lung cancer admitted to the ICU during a 23-year period decreased after 2015. Functional disability, advanced lung cancer stage, vasopressor use, and invasive mechanical ventilation predicted mortality.